Role of ley farming in crop rotations in the tropics - Mohamed-Saleem, M.A.; Fisher, Myles J. (New Zealand Grassland Association, 1993)
This paper examines one instance in tropical West Africa where Development agents encouraged ley farming as a means of intensifying crop-livestock interactions and improving human welfare without adverse effects on the environment. The response of the farmer to the technology has been mixed. Adoption has been limited by high opportunity costs of growing forages, as well as inadequate technical knowledge and attempts on the part of Development agents to export technologies outside their ecozonal limits. Neverthless, evidence of voluntary and government-credit-backed adaptation of ley farming concepts to producer circumstances is not difficult to find in such West African countries as Nigeria and Mali. This should not, however, be construed as an indication of future trends in ley farming, since agricultural production in the region is subsistence oriented and farmers are content with the present livestock herding practices and see no urgency to introduce soil restoration alternatives, as there are no visible manifestations of rapid environmental degradation. Constraints to leys and technology transfer are discussed.